Awareness and Attitudes of Customers Towards Islamic Banking Products in Non-Muslim Country: The Case Study of Cameroon (Journal of Economics, Law and Society, 2025)
The objective of this study is to examine the level of potential customers awareness and attitude towards Islamic banking products in Cameroon as a non-Muslim country. This research used mix method approach. First, Primary data obtained from Structured questionnaire with 300 respondents are analyzed using appropriate tools in order to examine customers level of awareness and their attitude. Secondly, the study used qualitative by interviewing 10 experts in Islamic finance. Potential customers awareness towards Islamic banking products is very low in Cameroon. They are only aware of the basics difference between Islamic banking and conventional banks. Unfortunately, they don’t know the principles and operation of Islamic banking products. Their level of knowledge is limited to the fact that Islamic banks operate without interest while conventional banks charge interest. Although they have low level of awareness, they have a positive attitude towards Islamic banking. Consequently, there are willing to patronize Islamic banking. This study is only limited in Muslim zone with the the targeted non users of Islamic banking products. The results of this study fill the existing gap in literature in Cameroon about Islamic banking in general and specifically customers awareness. It provides managerial implications at the level of Islamic finance operators. Meanwhile, this research provides some policy recommendations that can help boost the development of Islamic finance in Cameroon and promote financial inclusion. There is no prior research about potential customers awareness and attitude toward Islamic banking products in Cameroon. Therefore, this study remains the first one to be conducted.